Supply chain partnering practices among manufacturing firms in Malaysia: A conceptual approach - Chinniah, Muruga; Rajagopal, Prekumar; Sundram, Veera Pandian Kaliani; Bhatti, Muhammad Awais (2013)
Purpose: This paper aims to identify and discuss a robust conceptual framework on Supply Chain partnering and the various factors that enable its partnering efforts.Design/Methodology/Approach: Analyzing several research frameworks from various sources of literature in order to obtain the measurement instrument for major independent variable that supports the Supply Chain Partnering efforts.Findings: Analyzing information from literature search, have identified three major independent variable that supports the Supply Chain Partnering efforts; 1) Organizational Linkage, 2) Information Flow and 3) Resource sharing.Key success moderating variables are 1) Company’s line of business by Value Chain activity, 2) Industry experience, 3) Range of Products and World Best Practice Research Limitations / Application: Supply chain partnering is found to be an important ingredient to ensure close collaboration between supply chain members. Nevertheless, there are limited studies in this area.As such, identifying literature pertaining to supply chain partnering and its enabler is of challenge.Practical Implication: It is important for supply chain managers and practitioners to place specific attention in developing Supply Chain partnership in an attempt to gain, cost saving, efficiency and competitive advantage, especially among firms in the Electrical and Electronic industries.Originality/ Value: In addition this framework brings out the fact that Supply Chain Partnering can be effectively applied in the areas of Demand Forecasting & Planning, Procurement, Outsourcing and Inventory Management, which are directly link to maximizing profits.